Treatment efficiency and VFA composition of a thermophilic anaerobic contact reactor treating food industry wastewater - Senturk, E.; İnce, Mahir; Engin, G. Onkal (Elsevier, 2010)
The objective of this study was to examine the effects of organic loading rate and hydraulic retention time on volatile fatty acid composition and treatment efficiency of high rate thermophilic anaerobic contact reactor (TACR) treating potato-chips wastewaters. The operational performance of TACR was monitored from start-up by assessing chemical oxygen demand (COD) removal efficiencies, volatile fatty acid (VFA) production and biogas composition. The reactor was studied at different organic loading rates (OLRs) ranging from 0.6 to 8 kg COD/m(3) d. The COD removal efficiencies were found to be 86-97% and the methane percentage of the biogas produced was 68-89% during the OLRs studied. The approximate methane yield was found to be 0.42 m(3) CH4/kg CODremoved. The major intermediate products of anaerobic digestion were acetate, propionate, iso-butyrate, butyrate, iso-valerate, valerate, iso-caproate and caproate. The use of thermophilic anaerobic contact reactor offers a sustainable technology for the treatment of potato-chips wastewaters since high COD removal efficiencies and high methane percentage in the biogas produced can be attained even at high OLRs. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Thermophilic; Anaerobic contact reactors; Volatile fatty acids; Organic loading rate; Hydraulic retention time; Potato-chips wastewater